Produção das cidades e fragmentação socioespacial em tempos de COVID-19: análise do Setor Leste da cidade de Uberlândia-MG - Silva, Flaviane Fernandes Bernardes (2021)
This paper aims to understand the changes in the spatial configuration of the east sector of Uberlândia-MG, considering the implementation of private enterprises, irregular subdivisions and settlements, intensifying the processes of socio-spatial fragmentation in the context of urbanization in the city between the 1990s and 2020s and the increase in social inequalities during the COVID-19 pandemic. The fragmentation of urban spaces are extremely important processes in the context of contemporary urban dynamics in Brazilian cities. The socio-spatial inequalities in cities became more evident with the advance of the pandemic, the inhabitants of the peripheral areas are more vulnerable and feel the catastrophic effects of the Coronavirus. Contemporary urban space reinforces the systemic projects of the expanded reproductive model of wealth, in which power, capital and possession guide strategic actions of public policies, planning and actions in the urban space. Thus, cities are the materialization of social form, expressed through systems of ideas and thoughts, reverberating their complex meanings. The city of Uberlândia is located in a strategic geographic position, that is, between the connecting axes of the Southeast/South macro-regions to the Brazilian Midwest. The Eastern Sector stands out for its territorial and population extension, as well as its importance in the recent dynamics and diversity of capital and social reproduction of urban space in the city. For the application of the concept of socio-spatial fragmentation, two sections of the urban space in the eastern sector were defined, an area of concentration of closed horizontal condominiums and an area entitled ―Residential Integration‖, with the presence of irregular subdivisions and areas of irregular settlements. In view of the occurrence of the Sars-CoV-2 virus pandemic, naming the disease COVID-19, we identified the evolution of the pandemic, its vulnerabilities and the relationship with urban areas of Uberlândia, as well as the eastern sector of the city, intensifying social inequalities and the process of fragmentation in the urban space. The advance of COVID-19 in Brazil shows traces of a pandemic of class, gender and race, in which social and economic aspects are decisive and located on the urban fringes, with patterns of confirmed cases and death records. The methodological paths are highlighted by the steps of bibliographic research, survey and data tabulation, documental research, field research, application of electronic questionnaires, photographic records and production of maps. The thesis results were structured in four chapters, whose research highlights the analyzes and processes of socio-spatial fragmentation, as well as the inequalities and social vulnerability in pandemic times, it is worth noting that the socio-spatial fragmentation precedes the sanitary crisis of the pandemic, affecting its distribution and intensifies the spatialization of COVID-19 to areas of greater social vulnerability in urban spaces.